2000
DOI: 10.1128/jb.182.18.5147-5152.2000
|View full text |Cite
|
Sign up to set email alerts
|

Essentiality, Expression, and Characterization of the Class II 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase of Staphylococcus aureus

Abstract: Sequence comparisons have implied the presence of genes encoding enzymes of the mevalonate pathway for isopentenyl diphosphate biosynthesis in the gram-positive pathogen Staphylococcus aureus. In this study we showed through genetic disruption experiments that mvaA, which encodes a putative class II 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, is essential for in vitro growth of S. aureus. Supplementation of media with mevalonate permitted isolation of an auxotrophic mvaA null mutant that was att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 39 publications
3
89
0
Order By: Relevance
“…12,14 The results of this study revealed that farnesol inhibited class II HMG-CoA reductase. Statin is known to inhibit HMG-CoA reductase.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…12,14 The results of this study revealed that farnesol inhibited class II HMG-CoA reductase. Statin is known to inhibit HMG-CoA reductase.…”
Section: Resultsmentioning
confidence: 74%
“…12 HMG-CoA + NADPH + 2H + ! mevalonate + CoASH + 2NADP + Assays contained 0.25 mM NADPH, 0.25 mM HMG-CoA, 50 mM NaCl, 1 mM EDTA and 25 mM KH 2 PO 4 (pH 7.5).…”
Section: Hmg-coa Reductase Assaymentioning
confidence: 99%
“…Genomic analyses have revealed that staphylococci, streptococci, enterococci, and Archaea possess the enzymes of the mevalonate pathway but not of the glyceraldehyde 3-phosphate-pyruvate pathway, whereas Bacillus subtilis and most Gram-negative bacteria studied possess only components of the glyceraldehyde 3-phosphate-pyruvate pathway (28). Gene inactivation experiments of mvaA, which encodes a class II 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, have shown that mvaA is essential for in vitro growth of S. aureus and that the mutant used is attenuated for virulence in a murine hematogenous pyelonephritis infection model (29). In the various S. aureus genomes sequenced, seven identified genes are involved in the mevalonate pathway, based on sequence similarities and biochemical studies (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the various S. aureus genomes sequenced, seven identified genes are involved in the mevalonate pathway, based on sequence similarities and biochemical studies (30). The following reactions have been proposed: 1) condensation of two molecules of acetyl-CoA to form acetoacetyl-CoA, catalyzed by acetyl-CoA acetyltransferases; acetyl-CoA acetyltransferase homologues (SA0223) are present in various staphylococcal genomes; 2) Claisen condensation of acetyl-CoA with acetoacetyl-CoA to yield HMG-CoA, catalyzed by HMG-CoA synthase; the crystal structure and catalytic mechanism of the S. aureus HMG-CoA synthase (encoded by mvaS) have been investigated (30); 3) reduction of HMG-CoA to mevalonate, catalyzed by HMG-CoA reductase (encoded by mvaA) with NADPH as cofactor; HMG-CoA reductase is the best characterized enzyme of the mevalonate pathway in both eukaryotes and prokaryotes (29), and crystal structures have been solved for both human and bacterial HMG-CoA reductase; the eukaryotic HMG-CoA reductase is the target of the statin class of cholesterol-lowering agents; 4) Phosphorylation of mevalonate with ATP to form mevalonate-5-phosphate and then in a second reaction mevalonate diphosphate, catalyzed by mevalonate kinase; mevalonate kinase from S. aureus (mvaK1) has been characterized recently (31); 5) decarboxylation of mevalonate diphosphate to isopentenyl diphosphate, catalyzed by mevalonatediphosphate decarboxylase (encoded by mvaD); 6) isomerization of isopentenyl diphosphate to produce dimethylallyl diphosphate in the presence of both FMN and NADPH, catalyzed by a type II isopentenyldiphosphate isomerase (encoded by fni); this type II enzyme was first described by Kaneda et al (32); and 7) condensation of isopentenyl diphosphate and geranyl diphosphate to form farnesyl diphosphate, catalyzed by farnesyl-PP synthase (encoded by ispA).…”
Section: Discussionmentioning
confidence: 99%
“…Wilding et al (2000a) verified the essential requirement of the mevalonate pathway gene mvaA, which encodes the well-characterized and rate-limiting enzyme HMG-CoA reductase (Bochar et al, 1999). Initial attempts to delete this gene were unsuccessful, and the mevalonate pathway mutant could only be recovered when the medium was supplemented with exogenous mevalonate (Wilding et al, 2000a). Voynova et al (2004) (Laupitz et al, 2004).…”
Section: Isoprenoid Biosynthesis In Pathogensmentioning
confidence: 99%